Analysis of the attributions of physical therapists and physical educators in the home care of patients after Covid-19 (Research, Society and Development, 2021)
The coronavirus disease that has affected the world population had a high rate of recoveries in 2021, according to data from the Ministry of Health. The sequelae that affect the recovered patients mainly involve dyspnea, muscle fatigue, neurocognitive difficulties, and consequently a decrease in physical conditioning. After the hospital period, it is necessary that the patients seek professionals for treatment, where home-care has had great prominence. The multidisciplinary follow-up is extremely important, where the objective of this review is to present the contributions and differences in the home care of patients after Covid-19 of physical therapists and physical educators, who despite having similarities regarding the use of physical exercises in their care, the therapeutic goals are divergent, however, both contribute significantly in the stages of home rehabilitation. The federal councils are the ones that determine the attributions of each one in the treatment of this pathology, because although the studies involving the SARS-CoV-2 virus are still in process, there is evidence of the benefits provided by each professional in the post-hospital phase.